Empowering Local Institutions for Clean Water Management and Fire Risk Reduction in Kampung Adat Kuta, Ciamis - Indratno, Imam; Chovyan, Ivan; Adwiyah, Rabiatul; Kuntoro, Sena Hari (Journal of Social Science and Business Studies, 2025)
This study aims to strengthen clean water governance and fire risk reduction in Kampung Adat Kuta, Ciamis Regency, West Java, through a community-based empowerment approach. Using a participatory Community Partnership Program (PKM), the methods included community socialization and problem mapping, technical training for 20 residents, installation of a simple hydrant and clean water distribution network using HDPE pipes, and institutional strengthening through the establishment of a Community Water Management Group (KPA) and Standard Operating Procedures (SOPs). The results show increased technical capacity and awareness among residents, the formation of a functional local water management institution, and the availability of infrastructure supporting both daily water needs and fire emergency response. The program demonstrates that integrating local wisdom with appropriate technology effectively enhances community resilience. In conclusion, the Kampung Adat Kuta experience offers a replicable model of community-based water governance that supports heritage preservation, disaster risk reduction, and sustainable tourism development.